Host range and specificity of the Drosophila C virus. - Martin Kapun; Viola Nolte; Thomas Flatt; Christian Schlötterer (PLoS ONE)
Background The Drosophila C virus (DCV) is a common and well-studied Drosophila pathogen. Although natural infections are known from Drosophila melanogaster and D. simulans, and artificial infections have been reported from several Drosophila species and other insects, it remains unclear to date whether DCV infections also occur naturally in other Drosophila species. Methods/principal findings Using reverse transcription PCR, we detected natural infections in six Drosophila species, which have not been previously known as natural hosts. By subsequent Sanger sequencing we compared DCV haplotypes among eight Drosophila host species. Our data suggest that cross-infections might be frequent both within and among species within the laboratory environment. Moreover, we find that some lines exhibit multiple infections with distinct DCV haplotypes. Conclusions Our results suggest that the natural host range of DCV is much broader than previously assumed and that cross-infections might be a common phenomenon in the laboratory, even among different Drosophila hosts.